2008
DOI: 10.1099/ijs.0.65632-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium oryzae sp. nov., isolated from the wild rice Oryza alta

Abstract: During a study of endophytic nitrogen-fixing bacteria present in the wild rice species Oryza alta, eight novel isolates were obtained from surface-sterilized roots and classified in the genus Rhizobium on the basis of almost-complete 16S rRNA gene sequence analysis. These strains can nodulate Phaseolus vulgaris and Glycine max. The highly similar protein patterns, DNA fingerprint patterns of insertion sequence-based PCR (IS-PCR) and DNA-DNA hybridizations showed that these novel isolates were members of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 40 publications
1
44
0
1
Order By: Relevance
“…Rhizobium soli DS-42 T neither forms nodules nor is confi rmed to have the nodD and nifH genes (Yoon et al, 2010). Peng et al (2008) isolated Rhizobium oryzae Alt 505 T from the wild rice species of Oryza alta instead of leguminous plants, and did not amplify the nodD and nifH genes nor carry out the nodulation tests. Nodule induction and amplifi cation of nodD and nifH genes of Rhizobium selenireducens LMG 24075 T were both negative (Hunter et al, 2007).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Rhizobium soli DS-42 T neither forms nodules nor is confi rmed to have the nodD and nifH genes (Yoon et al, 2010). Peng et al (2008) isolated Rhizobium oryzae Alt 505 T from the wild rice species of Oryza alta instead of leguminous plants, and did not amplify the nodD and nifH genes nor carry out the nodulation tests. Nodule induction and amplifi cation of nodD and nifH genes of Rhizobium selenireducens LMG 24075 T were both negative (Hunter et al, 2007).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…103 Other species have been isolated from plant rhizosphere such as and R. alamii 104 and plant root inner tissues as R. oryzae. 105 The complete list of valid species of rhizobia is recorded in the List of Prokaryotic Names with Standing in Nomenclature that is performed …”
Section: Recent Changes In the Taxonomy Of Rhizobiamentioning
confidence: 99%
“…Aquatic leguminous plants have also been reported to harbour species of the genus Rhizobium (Zurdo-Piñeiro et al, 2004). Previous studies showed that novel species of the genus Rhizobium can also be found as endophytes colonizing roots of nonleguminous plants including rice, wheat and maize (Peng et al, 2008;Rosenblueth & Martínez-Romero, 2004;Schloter et al, 1997;Zhang et al, 2011b). Their role in promoting growth of non-leguminous plants has also been proposed (Yanni et al, 1997).…”
mentioning
confidence: 99%